2014
DOI: 10.1002/cbic.201402356
|View full text |Cite
|
Sign up to set email alerts
|

Application of Room‐Temperature Aprotic and Protic Ionic Liquids for Oxidative Folding of Cysteine‐Rich Peptides

Abstract: The oxidation of the conotoxin μ-SIIIA in different ionic liquids was investigated, and the results were compared with those obtained in [C2 mim][OAc]. Conversion of the reduced precursor into the oxidized product was observed in the protic ILs methyl- and ethylammonium formate (MAF and EAf, respectively), whereas choline dihydrogenphosphate and Ammoeng 110 failed to yield folded peptide. However, the quality and yield of the peptide obtained in MAF and EAF were lower than in the case of the product from [C2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 73 publications
6
48
0
Order By: Relevance
“…Among the various choices of ILs, ammonium-based ILs are seen to be most encouraging and safer alternative which can be used for the growth of pharmaceutical and various medical related applications [45][46][47][48][49][50][51][52][53][54] …”
Section: Important Application Of Ammonium-based Ils In Different Scimentioning
confidence: 99%
“…Among the various choices of ILs, ammonium-based ILs are seen to be most encouraging and safer alternative which can be used for the growth of pharmaceutical and various medical related applications [45][46][47][48][49][50][51][52][53][54] …”
Section: Important Application Of Ammonium-based Ils In Different Scimentioning
confidence: 99%
“…Therefore, an established protocol of partial reduction combined with carbamidomethylation was applied. [24] After sequencing of the linear, reduced peptide as control (Supporting Fig. S3A), the buffer-oxidized peptide was analyzed and the following connectivity was confirmed: C3-C21, C10-C25, C20-C29, corresponding to the suggested fold reported earlier (Supporting information, Supporting Fig.…”
Section: Peptide Synthesis and Chemical Characterizationmentioning
confidence: 99%
“…Only very few biotransformations have already been successfully carried out in neat ILs; as an example, Lozano, Vaultier, and co‐workers reported a pronounced stabilization effect of the enzyme α‐chymotrypsin in transesterification reactions . Recently, in another case, Imhof and co‐workers have found that oxidative folding of certain cysteine‐rich conotoxin peptides went along successfully only in the IL [emim]OAc, although various other ILs have been tested …”
Section: Biotransformationsmentioning
confidence: 99%
“…[49] Recently,i na nother case, Imhof and co-workersh ave found that oxidative folding of certain cysteine-rich conotoxin peptides went along successfully only in the IL [emim]OAc, although variousother ILs have been tested. [50] In summary,o ne can say that the combination of biotransformations and ionic liquidsh as great potentialf or future applications. To date, unfortunately,g eneral trends or even sensible conclusions are not yet available.…”
Section: B Iotransformationsmentioning
confidence: 99%